The position of non-muslim minorities in Turkey in Ziya Gökalp’s thought system - Alagöz, Helin (My University, 2006)
Ulus-devletlerin dogusu ile birlikte azinliklar meselesi uluslararasi iliskilerin alanina girmistir. Ancak azinliklar hakkinda yapilan çalismalar özellikle son yillara mahsus olup nispeten yenidir. Bu tez, Ziya Gökalp’in çalismalari üzerinden giderek, Osmanli Devleti’nin son yillari ile Cumhuriyet’in ilk yillari arasindaki dönemde, Türk milliyetçiliginde gayrimüslim azinliklarin konumunu incelemistir. Bu çalisma Ziya Gökalp’in milliyetçilik modelini yeni bir metodolojik bakisla incelemistir. Kullanilan metodoloji kronolojiktir ve Gökalp’in yazilarini iki asamada analiz etmistir. Ilk asama Gökalp’in 1914–1918 arasinda yazdiklarini, ikinci asama ise 1918–1924 arasinda yazdiklarini kapsamaktadir. Bu iki asamali analiz ile tarihsel ve düsünsel gelismelerin Gökalp’in düsünceleri üzerindeki etkisi de gözlemlenmistir. Gökalp’in Türklük hakkindaki düsüncelerinin dislayici olmadigi, dolayisiyla gayrimüslim azinliklari da Türkçe konusmak, Türk kültürünü paylasmak ve Türklük ideali için çalismak kosuluyla kapsadigi görülmüstür. The issue of minorities has entered the field of international relations with the emergence of nation states. However research on minorities is a relatively new phenomenon, seen in the last few decades. This thesis aims to demonstrate the position of non-Muslim minorities within Turkish nationalism in the late Ottoman and Early Republican contexts, drawing mainly on the work of Ziya Gökalp’s texts. By doing so, this study employs a new methodological perspective for looking at Ziya Gökalp’s nationalism model. This methodology is chronological, and is based on an analysis of two phases; Gökalp’s work from 1914 to 1918, and Gökalp’s work from 1918 to 1924. This two phased analysis underlines the influence of historical and intellectual developments on Gökalp’s ideas. This study emphasizes that Gökalp’s view of Turkishness is inclusive in form, since it does not exclude non-Muslim minorities in the condition that they speak Turkish, share the Turkish culture, and work for the Turkish “ideal
Keywords: Azınlıklar_Türkiye